An empirical analysis of globalization, oil receipts and health expenditure in Nigeria - Akintunde, T.; Adagunodo, M. (Journal of Economic Research & Business Administration, 2020)
This study examined the effect of globalisation and oil revenue on health expenditure in Nigeria. The study used annual time series data spanning from 1980 to 2018. Unit root test was used to check the stationary level of the variables and Unrestricted Error Correction Model (UECM) and Dynamic Ordinary Least Square (DOLS) were used to estimate the model. The dependent variable was health expenditure while the explanatory variables were globalisation, oil revenue, health care price, per capita income, life expectancy, mortality rate urbanization and corruption. The result showed that oil receipt had a long run and positive impact on health expenditure in Nigeria. However, globalisation had a negative and significant impact in the long-run though not significant in the short run. The implication is that both oil revenue and globalisation are still very important variables influencing health expenditure in Nigeria. It is recommended that government should increase allocation to the health sector from oil fiscal revenue so as to improve access to health care services in Nigeria. Also, the government should work on how the country can benefit from globalisation through more export and less of import.